Locas : the Maggie and Hopey stories. - Hernandez, Jaime (Love and rockets, 2026)
"Locas tells the story of Maggie Chascarrillo, a bisexual, Mexican-American woman attempting to define herself in a community rife with class, race, and gender issues. Maggie's story begins in the early-1980s Southern California rock scene, when it was shifting from the excesses of the 1970s to the gritty basics of punk and new wave. Hardcore punk rock came to the fore, and the teenage Maggie finds herself drawn to the anarchy, energy, and diversity of the scene, which in Jaime's hands becomes a very real, habitable place populated with authentic human beings rather than stereotypes. She quickly befriends Hopey Glass, a feisty anti-authoritarian punkette who quickly becomes Maggie's on-again, off-again lover and a constant presence in her life as they navigate a devastatingly naturalistic world."--Amazon.com